PENGARUH FAKTOR INTERNAL DAN EKSTERNAL PERUSAHAAN TERHADAP AUDIT REPORT LAG (Studi Empiris pada Perusahaan Non-financial yang Terdaftar di Bursa Efek Indonesia Tahun 2012) - Fina Ayu Shabrina; Shiddiq Nur Rahardjo (Diponegoro Journal of Accounting, 2014)
Timeliness of corporate annual financial reports is an important factor that affect to the usefulness of information in the financial reports to be used by stakeholders for decision-making. The length of audit process led to the emergence of Audit Report Lag (ARL), which is the time gap between the date of accounting financial year end and the date issuance of audited financial report. The purpose of this study is to analyze the factors: audit committee size, audit committee meeting, audit committee independence, audit committee qualification, company size, firm performance, auditor type, and audit opinion that affect to ARL. The populations in this study are all non-financial companies listed on the Stock Exchange in 2012. Sampling in this study using stratified proportional random sampling method. The total numbers of samples were 200 companies. Data used in this study was company’s annual financial reports that were derived from sites Indonesia Stock Exchange. Then, data were analyzed using multiple linear regression analysis. The result of this study shows that only factor audit committee size, audit committee qualification, company size, and audit opinion has significant influence on the ARL. While other factors, audit committee meeting, audit committee independence, firm performance, and auditor type has no significant effect on the ARL.